DISIPLIN KERJA DAN MOTIVASI KERJA UNTUK MENDUKUNG KINERJA PNS PADA KANTOR DINAS SOSIAL PROVINSI JAWA TENGAH - Sugeng sugeng-sutrisno@untagsmg.ac.id (FEB UNTAG Semarang, 2019)
The research is tested the influence of discipline and motivations independent variables to performances indipendent variable. The research takes it sample about 167 of 323 people in social office of Central Java consist of sub administration division 24 people, sub social protection division 30 people, sub social development division 27 people, sub social rehabilitation division 33 people, sub social assurance assistance division 34 people, sub chief of human resource development 10 people and sub chief finance 9 people and interviewing 5 chief division and 2 chief officers. The sample was drawn by Proportionate Stratified Random Sampling Method, even though collecting data used likert method, it’s mean perception scale is distribution responding and it is a basic of determining value’s scale, that is five (5) ordinary scale category. The analysis technique uses instrument test (validity test and reliability test) to test the quality and consistency of measurement tools, model test / classic assumption test (multikolinearity test, heterokedastisity test and normality test) to fulfill the conditions that the equation of regression model can be accepted. Regression analysis and determination coefficient by SPSS version 11.5 is used to acknowledge the effect change of an independent variable and to notice contribution of independent variable to explain dependent variable. The result of validity test explains that (a) all variables are reliable (b) all indicators are valid (c) it doesn’t occur of classic assumption and (d) combination of two variables discipline and motivation is influenced on officers performance in Social Office Central Java Province. There’s a relation between discipline and motivation on officers performance Key Words : Discipline, Motivation, Officers Performance